Critical factors affecting the public land development: A systematic review and thematic synthesis. (June 2022) - Singhapathirana, Priyanwada Indeewaree; Hui, Eddie Chi Man; Jayantha, Wadu Mesthrige
Abstract: Public land ownership is a common practice in many countries across the world. Whereas some countries provide empirical evidence on effective utilization of public lands, recent studies from elsewhere reveal less-obvious forms of public land misuse in cities. There has not been any systematic analysis to examine the most critical and common factors across countries that can either facilitate or hinder the effective utilization of public lands. This study aimed to examine the critical factors affecting the effective utilization of public lands. A systematic review and thematic synthesis were carried out with 44 research articles published on Public Land Development (PLD) over the last two decades (2000–2019), which were retrieved through a systematic approach. The review identified eleven critical factors affecting the PLD. This critical review was instrumental in identifying the knowledge gaps in PLD. The absence of a critical inquiry into the practice of longstanding underutilization of public lands in various forms and its causative factors, especially in the developing Asian countries (e.g., India, Sri Lanka) is one of the prominent knowledge gaps in current scholarship. Likewise, a firm adoption of a relational approach to analyse the public land and rigorous analysis of networked relationships among critical elements of PLD have yet to be undertaken. Highlights: Eleven critical factors affecting the efficient use of public lands are identified. Land allocation strategy is the most extensively discussed factor related to PLD. Synthesizing critical factors and their relationships accentuate the knowledge gaps. Longstanding underutilization of public lands in Asia has been overlooked. A rigorous analysis of relationships among critical elements of PLD has yet to be undertaken.